Impact of Human Capital in Quality and Strategic Excellences - Khaled Mohammad Talal Banyhamdan, Nader Mohammad Aljawarneh, Mohammed A. Alomari, Mohammad Salameh Almasarweh, Ibrahim Mohammad Harafsheh, Ali Awad Alwagfi (International Journal of Advanced Science and Technology, 2020)
The study seeks to define the impact of human capital on quality and strategic excellence. To achieve this research purpose, there were 50 questionnaires valid for statistical analysis, adopting the quantitative approach. The questionnaire was used to measure human capital on quality and strategic excellence. The study concluded that there was a statistically significant correlation between Sustainable human capital on quality and strategic excellence. In light of the aforementioned results, the study recommended the Safeway Company of Jordan needs to focus its efforts towards obtaining the required and appropriate experiences from holders of higher degrees and those who acquire the required knowledge through their experiences in a manner that contributes to enhancing its human capital.